Modified SEC III protocol: vertical control related to patients' compliance with the chincup. (29th April 2020) - Montinaro, Federica; Nucci, Ludovica; Carfora, Marco; d'Apuzzo, Fabrizia; Franchi, Lorenzo; Perillo, Letizia
Summary: Objectives: To compare the short-term outcomes of modified SEC III protocol in growing patients in relation to their compliance with the chincup, matching them with an untreated Class III control group (CG). Materials and Methods: Thirty-four patients (mean age of 8.6 ± 1.2 years) with Class III dentoskeletal malocclusion treated with the modified SEC III protocol and divided into group 1 (G1, 18 subjects), reporting good compliance and group 2 (G2, 16 subjects) not compliant with the chincup. The records were analysed before treatment (T1) and after the orthopaedic phase (T2), with an interval period of about 1.3 ± 0.5 years. The CG consisted of 16 untreated subjects with Class III dentoskeletal malocclusion (mean age of 8.3 ± 1.4 years). The statistical comparisons among the three groups were performed with ANOVA with Tukey's post hoc tests. Results: Both G1 and G2, compared with CG, presented significant improvements in the sagittal skeletal relationships (ANB +2.5° and +2.5°, Wits +4.2° and +3.0°, respectively). G1 exhibited a significant more favourable control of vertical skeletal relationships when compared to G2 (Palatal Pl.–Mandibular Pl. −2.0°) that were associated with a statistically significant reduction of the gonial angle (ArGoMe −1.7°). Limitations of the study were its retrospective nature and the lack of evaluation of the long-term outcomes. Conclusions: Both groups of treated patients showed favourable sagittal skeletal improvement compared with controls. The use of chincup in patients with good compliance produced significantly greater control of the skeletal vertical dimensions compared with patients not compliant with the chincup.